Particle image velocimetry and digital image correlation for determining the elasticity modulus in wood - Cássio Humberto Lima; Francisco Carlos Gomes; Rodrigo Allan Pereira; Fernando Pujaico Rivera (Scientia Agricola, 2021)
ABSTRACT: Several non-destructive testing techniques have been improved and tested in recent years. The non-destructive testing techniques using particle image velocimetry (PIV) and digital image correlation (DIC) differ from conventional testing techniques, as they allow making measurements indirectly. In this study, the elastic modulus in wood beams of Eucalyptus grandis and Pinus oocarpa were determined using PIV and DIC. The application of PIV and DIC techniques occurred during the static bending tests, when the displacements were also measured by the conventional method. The applied load values allowed calculating the elasticity modulus. In all regions of analysis, the mean values of the elasticity modulus found by the DIC, PIV and conventional method are statistically equivalent. It is concluded that the PIV and DIC testing techniques can be used to determine mechanical properties of wood.